2018
DOI: 10.1371/journal.pone.0204875
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise on circulating tumor cells among patients with resected stage I-III colon cancer

Abstract: BackgroundPhysical activity is associated with a lower risk of disease recurrence among colon cancer patients. Circulating tumor cells (CTC) are prognostic of disease recurrence among stage I-III colon cancer patients. The pathways through which physical activity may alter disease outcomes are unknown, but may be mediated by changes in CTCs.MethodsParticipants included 23 stage I-III colon cancer patients randomized into one of three groups: usual-care control, 150 min∙wk-1 of aerobic exercise (low-dose), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…After 6 mo, a significant decrease was observed in tumour cells circulating in both low- and high-dose exercise arms. However, no exercise dose-response association was observed[149]. The mechanism underlying the effect of exercise against the circulating tumour cells is yet unknown.…”
Section: Biomarkers and The Effect Of Exercise On Patients With Crcmentioning
confidence: 99%
“…After 6 mo, a significant decrease was observed in tumour cells circulating in both low- and high-dose exercise arms. However, no exercise dose-response association was observed[149]. The mechanism underlying the effect of exercise against the circulating tumour cells is yet unknown.…”
Section: Biomarkers and The Effect Of Exercise On Patients With Crcmentioning
confidence: 99%
“…In breast cancer cells, ICAM-1 activation was lower after moderate-intensity electrical stimulation in vitro [14,15]. In cancer patients with an activity level of 150 or 300 min/week at 50%-70% of maximum heart rate (i.e., moderate-intensity exercise), ICAM-1 levels were lower, which in turn reduced the amount of circulating tumor cells in the vessels [48]. A recent review concluded that moderate-intensity endurance exercise in healthy people is associated with a decrease in adhesion molecules, whereas high-intensity endurance exercise is associated with an increased expression of these factors for several hours post-exercise [47].…”
Section: Moderate Versus High Intensity Physical Activitymentioning
confidence: 99%
“…Multiple factors, including host genetics [9], method of childbirth (i.e., by vaginal delivery or caesarian section) [10], age [8], nutrition [11], and antibiotic intake [8], have been suggested to affect the composition of the intestinal microbiota. Recent studies demonstrated the association between exercise training, i.e., a low-cost health strategy, and lower risks of colon cancer [12,13], a disease that is known to at least partly arise from imbalanced intestinal microbiota [4]. Therefore, exercise may also have potential for modifying the composition of the intestinal microbiota, although these studies did not directly examine the effect of exercise on intestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%